Interspeech 2016 2016
DOI: 10.21437/interspeech.2016-1095
|View full text |Cite
|
Sign up to set email alerts
|

Does the Importance of Word-Initial and Word-Final Information Differ in Native versus Non-Native Spoken-Word Recognition?

Abstract: This paper investigates whether the importance and use of word-initial and word-final information in spoken-word recognition is dependent on whether one is listening in a native or a non-native language and on the presence of background noise. Native English and non-native Dutch and Finnish listeners participated in an English word recognition experiment, where either a word's onset or offset was masked by speech-shaped noise with different signal-to-noise ratios. The results showed that for all listener group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
(20 reference statements)
1
4
0
Order By: Relevance
“…The noise manipulation of the stimuli that was used in this study allows us to analyze the results in terms of the importance of word-initial and word-final information for native and nonnative spoken-word recognition in the presence of background noise. In line with previous studies (e.g., Allopenna et al, 1998; Coumans, van Hout, & Scharenborg, 2014; McQueen & Huettig, 2012; Scharenborg, Coumans, Kakouros, & van Hout, 2016; Slowiaczek et al, 1987; van der Vlugt & Nooteboom, 1987), word-initial information seems to be more important for successful word recognition than word-final information. The results showed that the masking of word-initial information was more detrimental to spoken-word recognition than the masking of word-final information, leading to lower word recognition accuracies and higher numbers of different erroneous answers.…”
Section: Discussionsupporting
confidence: 91%
“…The noise manipulation of the stimuli that was used in this study allows us to analyze the results in terms of the importance of word-initial and word-final information for native and nonnative spoken-word recognition in the presence of background noise. In line with previous studies (e.g., Allopenna et al, 1998; Coumans, van Hout, & Scharenborg, 2014; McQueen & Huettig, 2012; Scharenborg, Coumans, Kakouros, & van Hout, 2016; Slowiaczek et al, 1987; van der Vlugt & Nooteboom, 1987), word-initial information seems to be more important for successful word recognition than word-final information. The results showed that the masking of word-initial information was more detrimental to spoken-word recognition than the masking of word-final information, leading to lower word recognition accuracies and higher numbers of different erroneous answers.…”
Section: Discussionsupporting
confidence: 91%
“…In multilingual countries or countries where the general population has a high level of proficiency in a particular non-native language, the general (student) population can participate in studies investigating word recognition in that non-native language. This allows for groups of participants with a homogeneous background (Brouwer et al, 2012;Cooke et al, 2008;Coumans et al, 2014;Ezzatian et al, 2010;Golestani et al, 2009;Jin & Liu, 2012;Scharenborg et al, 2016aScharenborg et al, , 2018aShimizu et al, 2001;Van Engen, 2010;Van Wijngaarden et al, 2002;Zhang et al, 2014). Also studies that specifically investigated early bilinguals tended to have a group of participants with homogeneous language backgrounds (Ezzatian et al, 2010;Mayo et al, 1997;Meador et al, 2000, Rogers et al, 2006.…”
Section: Selection Of the Native And Non-native Listener Groupsmentioning
confidence: 99%
“…Alternatively, the influence of contextual information needs to be minimised. This can be done by using isolated words (Coumans, van Hout, & Scharenborg, 2014;Golestani et al, 2009;Kaandorp, De Groot, Festen, Smits, & Overts, 2015;Scharenborg, Coumans, Kakouros, & Van Hout, 2016a;Scharenborg et al, 2018a;Takayanagi, Dirks, & Moshfegh, 2002), by presenting words in a fixed carrier phrase (Rogers et al, 2006;Shimizu et al, 2001;Warzybok et al, 2015), by using sentences that are grammatically correct but semantically meaningless (Ezzatian et al, 2010) or using a keyword spotting task in which sentences contain only a limited number of common words (Bradlow & Alexander, 2007;Cooke et al, 2008;Meador, Flege, & MacKay, 2000). For example, Golestani et al (2009) used isolated words in a priming paradigm, as this allowed them to separate the semantic level of speech from the syntactic and pragmatic levels present in sentences.…”
Section: A the Man Is Watching The Show On His Television B The Man Just Bought A New Televisionmentioning
confidence: 99%
See 2 more Smart Citations